Solution and solid state conformational preferences of a family of cyclic disulphide bridged tetrapeptides. Issue 1 (January 2017) - Berger, Nadja; Li, Fee; Mallick, Bert; Brüggemann, J. Thomas; Sander, Wolfram; Merten, Christian
Abstract: A set of cyclic tetrapeptides of the general form cyclo (Boc‐Cys‐Pro‐X ‐Cys‐OMe) withX beingL‐ /D‐Ala, L‐ /D‐Val, andL‐ /D‐Trp was synthesized. These peptides serve as model systems for structure elucidation in solution and feature a variety of structural motifs — namely a β‐turn with intramolecular hydrogen bonding interactions, cis / trans isomerism, and a disulphide bond. In this work, we performed a comprehensive structural analysis focussing on their β‐turn conformational preferences using NMR, VCD, and Raman spectroscopy. Our results provide evidence for a strong influence of a single stereocenter on the structures of the peptides whereas solvent polarity does not significantly affect them. Additionally, the solid state conformational preferences were studied by crystal structure analysis. Overall, a general trend for the conformational preferences of this set of peptides can be concluded from the results of the complementary investigations.